Rumex japonicus Houtt. Extract Suppresses Colitis-Associated Colorectal Cancer by Regulating Inflammation and Tight-Junction Integrity in Mice - Kim, Hee-Young; Seo, Ji Eun; Lee, Hanul; Bae, Chang-Hwan; Ha, Ki-Tae; Kim, Seungtae (Frontiers in Pharmacology, 2022)
Irritable bowel disease (IBD), which results in an elevated risk of colitis-associated colorectal cancer (CAC), is characterized by inflammation and barrier disruption of the gut. The genus Rumex has anti-oxidative and anti-inflammatory effects, and the roots of Rumex japonicus Houtt (RJ) have been traditionally used in East Asia to treat digestive problems. We investigated the protective effect of RJ against azoxymethane (AOM)-and dextran sulfate sodium (DSS)-induced CAC in C57BL/6N male mice. The mice were intraperitoneally injected with AOM on the first day and orally treated with 2% DSS for 2 weeks (on the third and sixth weeks). RJ extract (100 mg/kg) was administered to the mice in the RJ group for 4 weeks (from the third to sixth week), and all mice were sacrificed on the final day of the eighth week. Changes in morphology, tight junctions (TJs), inflammation-related factors in the colon and serum inflammatory cytokine levels were measured. The colons of AOM/DSS-treated mice were shorter and heavier than those of normal mice. The number of tumors in the colons of AOM/DSS-treated mice increased; however, RJ suppressed these changes. RJ also reduced the levels of tumor necrosis factor-α, interleukin (IL)-6, and IL-1β in the colon and serum, and it increased the level of IL-10 in the colon. Moreover, RJ inhibited the barrier disruption and apoptosis in the colons of AOM/DSS-treated mice. RJ effectively suppressed AOM/DSS-induced CAC by inhibiting tumor formation, inflammation, disruption of TJ, and apoptosis in the colon.